Migrant Entrepreneurs Between Colombia and Germany: Return, Strategies, and Expectations - Felipe Aliaga-Sáez; David Alberto García-Arango; Yvonne Riaño; Jovany Sepúlveda-Aguirre; David Betancur-Betancur (Social Sciences)
There is scant literature on migrants with an entrepreneurial background and who return to their country of origin. Using a transnational theoretical approach, we seek to contribute to research in this field by analysing the return strategies and expectations of Colombian migrant entrepreneurs participating in the Programme Migration and Diaspora (PMD). This programme is implemented by the Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ) GmbH (German Society for International Cooperation, Eschborn, Germany) on behalf of the German Federal Ministry for Economic Cooperation and Development (BMZ, Berlin, Germany). To this end, a mixed-methods study was conducted. Likert scale questionnaires and semi-structured interviews were applied to twenty-seven entrepreneurs participating in the programme, analysing quantitative and qualitative variables. Migrants seek to contribute to Colombia’s development through entrepreneurship, looking for various commercial connections for which security and planning conditions are necessary. They see entrepreneurship as sustenance, which in most cases results in transnational links between Germany and Colombia. For that to happen, contacts and acquired experiences are fundamental, as well as tangible and intangible resources, amongst which the information and support for entrepreneurship granted by GIZ stand out. Generally, it is essential to continue strengthening differentiated and comprehensive support strategies for all types of migrant entrepreneurs in destination countries.